Geometrical and material optimisation of deformed steel fibres: Spirally deformed fibres. (15th November 2019) - Hajsadeghi, Mohammad; Chin, Chee Seong
Highlights: The optimisation procedure of fibres using finite element analysis is presented. The effects of geometrical and material properties of fibres are considered. An empirical equation for the design of spirally deformed fibres is proposed. The fibre possesses slip-hardening response up to its complete withdrawal. Abstract: This paper presents an optimisation procedure of geometrical and material properties of steel fibres using the validated three-dimensional nonlinear Finite Element (FE) pullout model previously proposed by the authors. The FE model is employed as a virtual laboratory unit to investigate the pullout performance of steel fibres with various shapes such as hooked-end and spirally deformed steel fibres. The preliminary FE pullout analyses imply that the optimisation of the fibre with spiral configuration (adjustment of geometrical and material properties of the fibre) could result in an efficient high-performing steel fibre; hence such a fibre is selected for the optimisation procedure. In order to re-validate the numerical pullout model and further adjust its nonlinear parameters for enhancing the simulations prediction, a set of experimental pullout tests are conducted on four spirally deformed steel fibres with different geometrical properties. Extensive parametric studies are performed on the material and geometrical properties of the fibre to examine their effects on the fibre pullout performance. Moreover, an empirical equation is proposed for the estimation of fibre efficiency and optimum design of spirally deformed steel fibres in which geometrical and material properties are taken into account.